Call to Arms: Iran's Marxist Revolutionaries; Formation and Evolution of the Fada'is, 1964–1976: by Ali Rahnema (London: Oneworld, 2021). Issue 3 (3rd July 2022) - Davari, Arash
Abstract : This review essay interprets Ali Rahnema's Call to Arms: Iran's Marxist Revolutionaries: Formation and Evolution of the Fada'is, 1964-1976 through a fragment drawn from Amir Parviz Pouyan's treatise "The Necessity of Armed Struggle and the Refutation of the Theory of Survival." The fragment illustrates a peculiar aspect of Marxist guerrilla warfare in 1970s Iran: its emphasis on political education through political violence in lieu of conventional organizing. Rahnema recovers this history in Iran's most prominent leftist guerrilla group, the Fada'is, of which Pouyan was a founding member. This essay situates Rahnema's work in opposition to three prominent trends in the historiography of modern Iran and demonstrates the book's unresolved relationship to a fourth, an approach that privileges gender as an analytic. Precisely where Call to Arms succeeds in correcting the historical record, repudiating judgments directed against Pouyan's branch of the Fada'is, it overlooks the lifeworld of affect and ethics implied in the Pouyan fragment.